Effect of thermochemical non-equilibrium on the aerodynamics of an osculating-cone waverider under different angles of attack. (October 2017) - Liu, Zhen; Liu, Jun; Ding, Feng; Li, Kai; Xia, Zhixun
Abstract: In order to research the effect of thermochemical non-equilibrium on the aerodynamics of an osculating-cone waverider, thermochemical non-equilibrium flow and perfect gas model are employed to study the aerodynamics of an osculating-cone waverider under different angles of attack. The obtained results show that the slope of the oblique shock wave has little difference when considering the thermochemical non-equilibrium effect under the condition of zero angle of attack. However, under the condition of other attack angles, the slope of the oblique shock wave diminishes when considering the thermochemical non-equilibrium effect. Furthermore, the non-equilibrium effect moves the pressure center of the osculating-cone waverider forward by as much as 1.53% of the whole craft's length, which must be taken into consideration in the balance design of aircraft. Highlights: The non-equilibrium effect towards osculating-cone waverider has little attention. A comparison between non-equilibrium flow and perfect gas has been conducted. The comparison conducted considered different angles of attack. The thermochemical non-equilibrium effects make the shock layer thinner. The thermochemical non-equilibrium effects make the pressure center move forward.